2019
DOI: 10.1177/1055665619883151
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Care for Families Affected by Craniofacial Conditions: The Views of Nonspecialist Health Professionals

Abstract: Objective: A diagnosis of a congenital craniofacial condition can have a significant impact on the psychological well-being of the affected family. As the first health professionals likely to come into contact with families, nonspecialists, such as diagnostic sonographers, midwives, and health visitors play a crucial role in facilitating familial adjustment. Yet, previous research has demonstrated parental dissatisfaction with the care delivered by nonspecialists. The aim of this study was to investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It is not uncommon in research for fathers to be underrepresented, however, we are lacking important information when considering the unique role that a father plays in their child’s development and in supporting the family overall (Lamb, 2010). In a study of fathers of children with CL/P, Stock and Rumsey (2015) found that fathers are just as affected, and potentially in different ways to mothers, by their child’s diagnosis, and should be offered the same level of involvement in their child’s care, both in research and practice. Future research should devise creative recruitment strategies to widen participation and ensure that target populations are more adequately represented in craniofacial research.…”
Section: Implications For Future Research and Practicementioning
confidence: 99%
“…It is not uncommon in research for fathers to be underrepresented, however, we are lacking important information when considering the unique role that a father plays in their child’s development and in supporting the family overall (Lamb, 2010). In a study of fathers of children with CL/P, Stock and Rumsey (2015) found that fathers are just as affected, and potentially in different ways to mothers, by their child’s diagnosis, and should be offered the same level of involvement in their child’s care, both in research and practice. Future research should devise creative recruitment strategies to widen participation and ensure that target populations are more adequately represented in craniofacial research.…”
Section: Implications For Future Research and Practicementioning
confidence: 99%
“…Health and support professionals were purposively recruited to understand the experiences and perspectives of professionals who are familiar with common issues faced by families of a child with an appearance-affecting condition/injury. Existing research has previously explored the experiences of nonspecialists 25 ; thus, this group was not targeted in the present research.…”
Section: Recruitment and Participantsmentioning
confidence: 99%
“…Similar findings have been reported previously among adults with cleft lip and palate and other craniofacial conditions (Tovetjärn et al, 2012;Ardouin et al, 2021a), and suggest that a large number of adults may be receiving inappropriate treatment, no treatment at all, and/or facing long and frustrating referral times. While health professionals cannot be expected to possess specialist knowledge on every condition they treat, access to educational materials when needed may provide a broad understanding of craniosynostosis and reduce uncertainty surrounding the best approach to care (Stock and Costa, 2020), with the ultimate aim of improving adults' treatment experiences. Finally, adults with craniosynostosis reported more symptoms of general anxiety than norms, in addition to lower levels of optimism and resilience.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%